2016
DOI: 10.1111/ner.12397
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Blinded Pilot Testing of Nonconventional Stimulation Patterns and Shapes in Parkinson’s Disease and Essential Tremor: Evidence for Further Evaluating Narrow and Biphasic Pulses

Abstract: Objectives Evidence suggests that non-conventional programming may improve deep brain stimulation (DBS) therapy for movement disorders. The primary objective was to assess feasibility of testing the tolerability of several non-conventional settings in Parkinson’s disease (PD) and essential tremor (ET) subjects in a single office visit. Secondary objectives were to explore for potential efficacy signals and to assess the energy demand on the implantable pulse-generators (IPG). Materials and Methods A custom f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 47 publications
0
69
0
Order By: Relevance
“…While there are some irregular patterns that seem to be as effective as—or more effective than—regular HFS, evidence for human testing remains limited. A recent randomized, blinded pilot study of nonconventional DBS patterns and pulses—the first reported study of its kind—tested 3 essential tremor and 8 PD clinically-optimized patients in a clinic setting (Akbar et al, 2016). Of the settings tested, the nonconventional biphasic pulse (equal and opposite, active recharge phase) was shown to be more effective than the clinically optimized settings.…”
Section: Dbs Innovationsmentioning
confidence: 99%
“…While there are some irregular patterns that seem to be as effective as—or more effective than—regular HFS, evidence for human testing remains limited. A recent randomized, blinded pilot study of nonconventional DBS patterns and pulses—the first reported study of its kind—tested 3 essential tremor and 8 PD clinically-optimized patients in a clinic setting (Akbar et al, 2016). Of the settings tested, the nonconventional biphasic pulse (equal and opposite, active recharge phase) was shown to be more effective than the clinically optimized settings.…”
Section: Dbs Innovationsmentioning
confidence: 99%
“…DBS was delivered utilizing a custom temporary downloadable firmware compatible with Medtronic Activa neurostimulators (Medtronic Neuromodulation), using the previously published protocol by Akbar and colleagues . The parameters were based on chronic settings, and the stimulation mode was modified from the standard passive‐recharge biphasic to the sqBIP pulse shape, except for dual‐channel devices with different settings for each of the leads (i.e., attributed to technical limitations from the software the investigator adopted the lowest of the 2 settings to ensure patient safety).…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, Akbar and colleagues investigated several novel stimulation parameters in essential tremor (ET) and Parkinson's disease (PD) patients using a blinded, randomized design. The researchers reported that square biphasic (sqBIP) pulses (with active rather than passive charge‐balancing phase) were well tolerated and provided a greater clinical benefit when compared to continuous commercially available DBS.…”
mentioning
confidence: 99%
“…Also, pulse‐width modulation might provide clinical benefit in certain situations. By exciting thin axon bundles belonging to the direct cortico‐subthalamic pathway more selectively, therapeutic windows may increase using shorter pulse widths, while using less energy …”
Section: Future Considerationsmentioning
confidence: 99%